Prevalence and risk factors of hepatitis B virus infection in Middle‐Limburg Belgium, year 2017: Importance of migration. Issue 8 (25th March 2019) - Koc, Özgür M.; Kremer, Cécile; Bielen, Rob; Buscchots, Dana; Hens, Niel; Nevens, Frederik; Robaeys, Geert
Abstract: Background and Aim: The hepatitis B virus (HBV) prevalence study performed in 2003 in Belgium is believed to be underestimating HBV prevalence due to underrepresentation of the non‐Belgian population. Therefore, we assessed the prevalence and risk factors of HBV infection in a multi‐ethnic region situated in Middle‐Limburg Belgium, in 2017. Methods: Between May and November 2017, blood samples and questionnaires were taken from patients who presented at the emergency department of a large educational hospital. Blood samples were tested for hepatitis B surface antigen (HBsAg) and hepatitis B core antibodies (anti‐HBc). A sample size of 1000 persons was required to obtain a representative sample of the general Middle‐Limburg population. Results: Of the 1131 patients screened, the overall HBsAg prevalence was 0.97% with differences between Belgians (0.67%) and first‐generation‐migrants (2.55%), ( P = 0.015). Five (45.5%) of 11 HBsAg‐positive individuals were not aware of their HBV status. All five (100%) newly diagnosed HBsAg‐positive patients had further clinical evaluation and all had a normal level of alanine aminotransferase (ALT). The prevalence of anti‐HBc was 8.4%, and was significantly associated with age‐gender‐ethnicity interaction, presence of HBV‐infected household member, hepatitis C virus infection, men who have sex with men, and hemodialysis. Conclusions: In this area with large immigrant populations, we found a higher prevalence of HBV infection compared with the nationwide study of 2003. National HBV screening for first‐generation migrants is needed as this high‐risk group will go unnoticed due to the possible incorrect interpretation of normal ALT values. Highlights: Higher prevalence of HBV infection in an area with large immigrant populations. First‐generation migrants are an important risk group for HBV infection. Universal HBV vaccination reduces the prevalence of HBV infection. Majority of newly diagnosed chronic HBV patients have normal ALAT levels.